2022
DOI: 10.1098/rstb.2021.0074
|View full text |Cite
|
Sign up to set email alerts
|

Soil resistance and recovery during neotropical forest succession

Abstract: The recovery of soil conditions is crucial for successful ecosystem restoration and, hence, for achieving the goals of the UN Decade on Ecosystem Restoration. Here, we assess how soils resist forest conversion and agricultural land use, and how soils recover during subsequent tropical forest succession on abandoned agricultural fields. Our overarching question is how soil resistance and recovery depend on local conditions such as climate, soil type and land-use history. For 300 plots in 21 sites across the Neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 79 publications
0
20
0
1
Order By: Relevance
“…Framework species planting [53] was planned in areas > 100–300 m from nearby intact forest (< 40–80% deficit) and savanna/agro-ecological mosaic (< 40–50% deficit), where seed dispersal was assumed to be restricted [16,17,54]. Severely degraded sites with ≥ 95 ± 5% AGB deficit were assumed to require soil improvement ([55] and [56]) followed by planting pioneer, nitrogen-fixing plants to be replaced with native trees over time [19] Soil improvement and nurse planting≥ 95 (≥ 90 to ≥ 100)AnyAny…”
Section: Methodsmentioning
confidence: 99%
“…Framework species planting [53] was planned in areas > 100–300 m from nearby intact forest (< 40–80% deficit) and savanna/agro-ecological mosaic (< 40–50% deficit), where seed dispersal was assumed to be restricted [16,17,54]. Severely degraded sites with ≥ 95 ± 5% AGB deficit were assumed to require soil improvement ([55] and [56]) followed by planting pioneer, nitrogen-fixing plants to be replaced with native trees over time [19] Soil improvement and nurse planting≥ 95 (≥ 90 to ≥ 100)AnyAny…”
Section: Methodsmentioning
confidence: 99%
“…Although lower than the rainforests of Amazonia and Mata Atlântica [ 78 ], the potential total biomass stocks of restored W&F in the Cerrado are high, particularly at the transition zones at the edges of the region (electronic supplementary material, table S1 and figure S7) [ 44 , 72 ]. SOC content and soil quality indicators are often neglected in empirical tropical restoration studies [ 79 ] and understanding SOC gains or losses as a result of restoration will be critical for further prioritization attempts [ 80 , 81 ]. Although potential SOC gains from restoration are not included in our analysis, a recent study demonstrated that SOC gains in grassland vegetation under high CO 2 could be greater than those of forested areas, suggesting that tropical grasslands may be more important for long-term C storage in soils [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 97 ] demonstrate that root traits of planted trees can be used to predict species success in dry forests. Further new research in this theme issue shows how information on soils is necessary for tailoring restoration and remediation methods to local site conditions [ 70 , 98 ].…”
Section: Essential Science Advancesmentioning
confidence: 99%